LOCAL MARKETING IN TOURISM DEVELOPMENT: CASE STYDY IN PHU THO PRONVINCE, VIETNAM - Pham, Huong Thi Thu; Pham, Nga Thi; Sinh, Tran Thi Thuy (The journal of contemporary issues in business and government, 2021)
This study aims to analyze and evaluate the current situation of applying local marketing in tourism development in Phu Tho. The study uses primary and secondary data sources collected through a survey of 150 tourists to assess the local marketing factors that attract tourists in Phu Tho province. Research results have shown the destination image, attractiveness, tourism products, tourism products, prices of tourism services, promotion, tourism infrastructure, social environment, quality of tourism human resources of Phu Tho province which are evaluated well by visitors. However, there are still aspects that need to be improved, such as the quality of promotion, the professionalism of the tourism human resources, etc. Therefore, the study has suggested seven groups of solutions perfect local marketing tools and strengthen the application of local marketing in tourism development in the coming time.